Characterization of Arcobacter spp. isolated from retail seafood in Germany. (September 2019) - Zhang, Xiaochen; Alter, Thomas; Gölz, Greta
Abstract: Arcobacter species are considered emerging zoonotic pathogens associated with human gastroenteritis. They were already isolated from a wide range of habitats and hosts worldwide. However, information about the prevalence of Arcobacter in retail seafood products is still scarce. This study aimed to evaluate the presence of Arcobacter in retail seafood and characterize Arcobacter isolates derived from these matrices. In total, seven species of Arcobacter were isolated from 56 of 318 (17.6%) seafood samples, including bivalves (mussels, clams and razor clams), shrimps and cephalopods (squids and octopuses). The highest prevalence was detected in cephalopods (27.4%), followed by bivalves (18%) and lowest in shrimps (8.5%). PCRs of 10 putative virulence genes demonstrated higher prevalences of these genes among A. butzleri, compared to other species, such as A. cryaerophilus, A. aquimarinus and A. venerupis . Further, high genetic diversity could be determined by ERIC-PCR. Our study indicates the potential transmission of Arcobacter to humans by consuming uncooked or undercooked seafood. Highlights: Prevalence of Arcobacter in seafood is 17.6%. Seven different Arcobacter species were detectable in seafood. High genetic diversity of Arcobacter spp. in seafood was determined by ERIC-PCR.